2017
DOI: 10.21273/horttech03681-17
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Landscape Roses Grown with Minimal Input in the North-central, Central, and South-central United States

Abstract: Landscape roses (Rosa sp.) are popular flowering shrubs. Consumers are less willing or able to maintain landscape beds than in years past and require plants that are not only attractive, but well-adapted to regional climatic conditions, soil types, and disease and pest pressures. Marketing and distribution of rose cultivars occurs on a national level; therefore, it is difficult for U.S. consumers in the U.S. Department of Agriculture (USDA) Plant Hardiness Zones 3 to 5 to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
4
7
0
1
Order By: Relevance
“…Disease pressure was highest in the spring, with a recurrence of black spot in the fall, and virtually no disease pressure during July and August. Landscape performance of Buck roses was usually consistent with previous rose cultivar trials in northcentral Texas (Harp et al, 2019;Mackay et al, 2008;Zlesak et al, 2017). In this study, several rose cultivars performed well, especially April Moon, Freckles, Carefree Beautyä, Red Dream, Square Dancer, Prairie Breeze, and Country Dancer, whereas others performed poorly.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Disease pressure was highest in the spring, with a recurrence of black spot in the fall, and virtually no disease pressure during July and August. Landscape performance of Buck roses was usually consistent with previous rose cultivar trials in northcentral Texas (Harp et al, 2019;Mackay et al, 2008;Zlesak et al, 2017). In this study, several rose cultivars performed well, especially April Moon, Freckles, Carefree Beautyä, Red Dream, Square Dancer, Prairie Breeze, and Country Dancer, whereas others performed poorly.…”
Section: Discussionsupporting
confidence: 87%
“…2008; Zlesak et al, 2017), with the best performance and heaviest blooms found in spring (April and May), with plant recovery and a second bloom occurring in the fall (September and October). Disease pressure was highest in the spring, with a recurrence of black spot in the fall, and virtually no disease pressure during July and August.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations